2016
DOI: 10.21511/imfi.13(4-1).2016.11
|View full text |Cite
|
Sign up to set email alerts
|

The impact of macroeconomic factors on the real estate investment trust index return on Japan, Singapore and China

Abstract: The impact of macroeconomic factors on the real estate investment trust index return on Japan, Singapore and China AbstractThis study contributes to the existing literature by combining the multiple methods to clarify the influence of the macroeconomic factors on the real estate investment trust (REIT) index in three Asian countries. The authors, first, use an autoregressive distributed lag (ARDL) bounds test to find that a long-run equilibrium exists between the REIT index and the interest rate, inflation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…To capture this structural shift and its impact on illiquidity premiums, we split our sample into two sub-samples; December 2007 to June 2009 which is classified as the financial crisis period, and July 2009 to December 2018 which is classified as the post-crisis period. The ARDL bounds test can be applied to studies with a small size (Fang et al 2016), whereas, the Johansen (1988) approach is not suitable for small sample sizes (Mah 2000). Therefore, using the bounds test approach fits our study perfectly in terms of assessing a cointegration relationship, especially within the recession period.…”
Section: Introductionmentioning
confidence: 94%
“…To capture this structural shift and its impact on illiquidity premiums, we split our sample into two sub-samples; December 2007 to June 2009 which is classified as the financial crisis period, and July 2009 to December 2018 which is classified as the post-crisis period. The ARDL bounds test can be applied to studies with a small size (Fang et al 2016), whereas, the Johansen (1988) approach is not suitable for small sample sizes (Mah 2000). Therefore, using the bounds test approach fits our study perfectly in terms of assessing a cointegration relationship, especially within the recession period.…”
Section: Introductionmentioning
confidence: 94%
“…Liow, Zhou and Ye (2015) indicated that there are reasonable correlation dependencies between real estate securities and stock markets which are affected by macroeconomic factors. According to Fang, Chang, Lee and Chen (2016), the stock index has positive impacts on the REIT index in Japan, Singapore and China. Laopodis (2009) also investigated the interaction of REITs, the stock market and the real economy in the US market from 1971 to 2007 and found that REITs display similar characteristics to the movements in industrial production growth, implying that changes in policies impact the real economy, which in turn affect the returns on real estate stocks.…”
Section: Macroeconomic Factorsmentioning
confidence: 99%
“…Nittayagasetwat and Buranasiri (2012) checked the sensitivity of returns on REITs to information on interest rate of bond and stock market returns in US capital market and the study showed that REITs return were insignificantly sensitive to bond and stock information on their interest. Fei, Ding and Deng (2008) Feng et. al.…”
Section: _______________________________________________________ 311mentioning
confidence: 99%